Characterisation of fabric deformation mechanisms during preform manufacture - Blagdon, Mark (1998)
The use of composites for structural applications in the automotive industry has become more attractive due to the possible weight savings and part integration. Liquid moulding processes, where the reinforcement is prepared separately from the moulding operation, have been suggested as a suitable production method. However there are several obstacles to overcome before they can meet the high production volumes required. Whilst forming the preform, defects such as wrinkling and tearing can occur which can prevent successful moulding.